Tiktok as a Political Communication Medium: An Examination of the United Nations - Zindan Çakıcı (İletişim Kuram ve Araştırma Dergisi)
In contemporary society, TikTok has emerged as a preeminent platform increasingly used by political entities to facilitate the advancement of communication strategies and currently boasts over 1.1 billion active users. The United Nations (UN), established in 1945 as a quintessential international political institution, inaugurated an official TikTok account in 2020 in response to the exigencies imposed by the Covid-19 pandemic. An examination of the extant literature reveals a marked paucity of scholarly inquiries critically evaluating the UN's social media communication strategies, particularly a notable dearth of analyses specifically addressing the UN's strategic engagements on TikTok. This study aspires to augment the existing corpus of literature concerning TikTok's role in global communication by scrutinizing the UN's communication strategies on this platform. The research entails a content analysis of 287 posts disseminated via the UN's TikTok account from March 31, 2020, to October 26, 2024. The findings elucidate that the UN has adeptly constructed a digital communication strategy characterized by the extensive integration of elements, including subtitles, captions, music, and hashtag within its TikTok posts. Moreover, the analysis indicates that the UN endeavors to transmit salient messages to its audience through a diverse array of audiovisual formats and affective tonalities. However, it is also observed that the UN inadequately addresses the exigencies of marginalized populations on TikTok, manifesting disparities in representational equity for specific demographic cohorts and exhibiting insufficient adherence to the principle of multilingualism. Finally, the UN was found to have a clear bias in its TikTok content regarding global political issues, a stance evident in the framing of the content.